2020
DOI: 10.1051/0004-6361/202037982
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale cosmic web detachments, connectivity, and preprocessing in the supercluster SCl A2142 cocoon

Abstract: Context. Superclusters of galaxies and their surrounding low-density regions (cocoons) represent dynamically evolving environments in which galaxies and their systems form and evolve. While evolutionary processes of galaxies in dense environments are extensively studied at present, galaxy evolution in low-density regions has received less attention. Aims. We study the properties, connectivity, and galaxy content of groups and filaments in the A2142 supercluster (SCl A2142) cocoon to understand the evolution of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(95 citation statements)
references
References 172 publications
8
87
0
Order By: Relevance
“…We note that the term pre-processing is commonly used in the literature to refer to all environmental effects that could affect galaxies prior to their accretion into clusters (eg. Boselli et al 2005;Wetzel et al 2012;De Lucia et al 2012;Einasto et al 2020). This is, regardless of whether the result is the cease of their star formation or not.…”
Section: Quenching Of the Star Formationmentioning
confidence: 94%
“…We note that the term pre-processing is commonly used in the literature to refer to all environmental effects that could affect galaxies prior to their accretion into clusters (eg. Boselli et al 2005;Wetzel et al 2012;De Lucia et al 2012;Einasto et al 2020). This is, regardless of whether the result is the cease of their star formation or not.…”
Section: Quenching Of the Star Formationmentioning
confidence: 94%
“…The ID numbers of the richest clusters in the high-density cores of the supercluster are shown (Abell clusters A2065, A2061, and A2089, and cluster Gr2064 that does not belong to Abell). used by Einasto et al (2018aEinasto et al ( , 2020 in the analysis of supercluster SCl A2142.…”
Section: Supercluster Group and Filament Datamentioning
confidence: 99%
“…As candidates for the centres of attraction in the high-density cores of the supercluster, we chose the richest clusters above the global luminosity density level D8 ≥ 8. This threshold density level for high-density cores of CB was chosen on the basis of earlier studies of superclusters, which showed that rich superclusters contain high-density cores, while such cores are absent in poor superclusters (Einasto et al 2007b(Einasto et al ,a, 2015(Einasto et al , 2020. We searched for rich clusters from the group catalogue with D8 ≥ 8, and selected the richest of them as possible centres of attraction in the supercluster.…”
Section: Supercluster Group and Filament Datamentioning
confidence: 99%
See 2 more Smart Citations